Corporate Sustainability and Digitalization: Is It a Bank Performance Boosters? - Indayani, Indayani; Meuthia, Putri Zidni Ayu; Meutia, Rita (Jurnal Keuangan dan Perbankan, 2023)
The company's financial performance remains a contemporary issue and is of concern to stakeholders and investors. In terms of achieving the company's performance, the bank's management will carefully consider management decision. Thus, determining the right strategy is one of the important step to improving the financial performance of the corporate. Some of these strategies and management decisions in nonfinacial area are to carry out digital transformation and implement the Corporate Sustainability Program. A good company's financial performance is the proper and correct implementation of the strategy and applicable rules. Corporate Sustainability (CS) and digitalization have become important factors in this decade and their impact on banking financial performance. The objective of this study is to examine Corporate Sustainability (CS) and digitalization as the factors that can influence the bank’s financial performance.  The population of this research is 47 banks listed on IDX from 2013-2020. Then, The Sample selection was carried out by selecting banking companies that issued sustainability reports and a final sample of 6 banks was obtained with 48 total observation for 8 years. The data source is secondary data obtained from the sustainability report and financial statements of banks listed on the IDX and published in 2013-2020. The results showed that digitalization significantly affects the bank’s financial performance. In contrast, corporate sustainability does not significantly affect financial performance. This shows that in the long time during the observation period, corporate sustainability activities did not work to improve banking finance in Indonesia. The stakeholders are more concerned about other factors that can increase banking company performance. This could also be because a banking company is more profit oriented. They are reliant on financial factors other than sustainability  DOI : 10.26905/jkdp.v27i3.9756